KELOMPOK WANITA TANI (KWT) PELANGI KOPI SEBAGAI INOVASI PEMBERDAYAAN JANDA GUNA MENGENTASKAN KEMISKINAN DI DESA GIRI MULYO - Witro, Doli (KOMUNITAS, 2019)
This paper intends to explore further about the widow empowerment activities carried out by the Women Farmers Group (KWT) located in Giri Mulyo Village, Kayu Aro Barat District, Kerinci Regency. As it is known, KWT Pelangi Kopi aims to improve the lives of the people of Giri Mulyo Village by prioritizing women who are widows. KWT Pelangi Kopi focuses its activities on local agricultural products, such as coffee, oranges, and turquoise eggplants. Agricultural products are processed into various products to sell, so that it can increase the income of the members. This community is important and interesting to study, because the activities / programs they run are closely related to the poverty alleviation agenda and improving people's welfare which is an important agenda of the government, even in all countries in the world. This community has become even more interesting because its members are only women and are also managed by women. Thus, besides being related to poverty and welfare issues, this community is also closely related to women's empowerment.